(In)visible spaces : a home organisation campaign - Yong, Rachel Shu Hui (2016)
This paper details the social campaign, (In)visible Spaces, that is aimed at creating awareness of the effects of living in a cluttered space and ultimately promoting decluttering and organising of homes. This was achieved by conducting home organisation workshops that explained the cost of disorganisation and imparted practical skills to declutter and organise houses effectively. (In)visible Spaces was developed by four final-year students from the Wee Kim Wee School of Communication and Information at Nanyang Technological University. The primary target audience comprises of homeowners residing in Singapore aged 25 to 40 years. As people within this age group are largely new homeowners, they require the skill of organising so as to prevent the long term accumulation of clutter. Campaign tactics focus on workshops to add value to the target audience’s existing knowledge and skills. This campaign is the first of its kind in Singapore. The campaign was successful in motivating the audience to declutter – from 67.2% of motivated workshop participants before the session to 96.9% after. All post-workshop survey respondents (100%) also indicated their intentions to change after attending the event. Additionally, the topic attained high media attention and interest with 20 published magazine articles within a span of three months. Overall, our home organisation workshops prove that skills transfer and testimonials are effective mediums to encourage and induce positive behaviour change. This report also presents insights concluded from literature review, primary and secondary research that directed the campaign strategising. It records the campaign process from creative ideation to tactical planning and execution. Campaign evaluation was conducted using post-workshop surveys and participant testimonials as our effectiveness measure. The appendices provide additional references with original supporting documents, collateral designs, primary research results and media clippings.